Sobre a natureza em Ludwig Feuerbach - Bittencourt, Antonio Adriano de Meneses (2020)
Ludwig Feuerbach's thought follows a winding path from his youth to maturity, driven by an avid search for freedom. This freedom is not conditioned to a system, whether religious or philosophical. He finds nature in his true expression. Taking a path opposite to speculative thinking after having traveled between mysticism and speculation in his youth, Feuerbach does not start from ideas to things, on the contrary, he only sees the philosophical truth through the senses. In this work, we investigate, in some of his main works, as Thoughts on Death and Immortality (1830), The Essence of Christianity (1841), Principles of the Philosophy of the Future (1843) The Essence of Religion (1846), Lectures on the Essence of Religion (1848), Ethic and Happiness (1868) and Spiritualism and Materialism (1866), the elements that bring us closer to understanding what Feuerbach understood by Nature. A profound theme underlying the Philosopher's general thought, the concept of Nature in Feuerbach begins in his early writings as a critique of the immortality of the soul and the resizing of the human will, elements that prefigure his later reflections in the field of theology and religion. Feuerbach, referenced in the philosophical tradition of Idealism, but radically diverging from it, seeks to bring Nature to the forefront of philosophical reflections as a critique of the model that has been pursued throughout the history of philosophy since Descartes, which inherits elements of medieval thought, even Hegel, the pinnacle of idealistic philosophy. Our task, in addition to scrutinizing the works of Feuerbach to bring us closer to what this Author understands by Nature, is also to expose Feuerbach as an important name for the rescue of Nature as an ethical premise. However, the symbiosis between Nature and ethics is at the heart of Feuerbach's concerns, since the defense of the valorization of Nature is sustained in the philosophical context and, going further, makes it a prerequisite for understanding the notion of freedom, which, although expresses itself through man, is conditioned to the way the latter understands itself in its relationship with Nature, not making it something different from what it is, but immersing and extracting from it, through the immediate relationship that it establishes, reason the last one that ends the exclusive dependence of its essence.